Post-Traumatic Growth and Couple Resilience: Exploring the Mediating Role of Relational Meaning Making - Oliveira, Mariana; Fernandes, Lucas; Gruber, Lukas (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study aimed to examine whether relational meaning making mediates the relationship between post-traumatic growth and couple resilience among Brazilian couples who have experienced significant adversity or loss. Methods and Materials: A descriptive correlational design was applied with a sample of 404 adult participants from Brazil, recruited using the Morgan and Krejcie sample size guidelines to ensure adequate statistical power. Participants completed standardized instruments: the Posttraumatic Growth Inventory, the Dyadic Meaning-Making Scale, and the Couple Resilience Inventory. Data were analyzed using IBM SPSS Statistics version 27 to compute descriptive statistics and Pearson correlation coefficients and AMOS version 21 for Structural Equation Modeling (SEM) to test the hypothesized mediation model. Model fit was evaluated with multiple indices, including χ²/df, CFI, TLI, GFI, AGFI, and RMSEA. Findings: Post-traumatic growth showed a significant positive correlation with relational meaning making (r = .62, p < .001) and couple resilience (r = .54, p < .001). Relational meaning making was strongly associated with couple resilience (r = .68, p < .001). SEM results indicated good model fit (χ²/df = 1.78, CFI = .96, TLI = .95, RMSEA = .044). Post-traumatic growth had a direct effect on couple resilience (β = .27, p < .001) and on relational meaning making (β = .62, p < .001). Relational meaning making had a strong direct effect on couple resilience (β = .63, p < .001). The indirect effect of post-traumatic growth on couple resilience through relational meaning making was significant (β = .39, p < .001), increasing the total effect of post-traumatic growth on couple resilience (β = .66, p < .001). Conclusion: Findings suggest that while post-traumatic growth contributes to couple resilience, its impact is amplified when partners engage in shared sense-making about adversity. Strengthening relational meaning making may be a key therapeutic mechanism for enhancing resilience in couples coping with trauma.